MODELS OF FOREIGN LANGUAGE TEACHER EDUCATION IN THE USA - Levrints (Lőrincz) (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The present paper considers current models and approaches of foreign language teacher education in the USA, which are further classified on the basis of their underlying criteria. Finally, a taxonomy of foreign language teacher education models is proposed: 1. according to the chronological criterion, the intuitive, behaviourist or art-craft, applied science, reflective, and critical models are differentiated; 2. according to the conceptual criterion, the science-research, theory-philosophy, and art-craft models are singled out; 3. according to the prevalent aim of teacher education, the differentiation between technicist, reflective and critical models is made; 4. according to the conceptual underpinnings of professional knowledge base and approaches to the education of teachers, the two most widely recognised are the transmission and collaborative models; 5. according to the epistemological criterion which underlies the mainstream approaches in the practice of language teacher preparation the following models are widely discussed in the relevant academic literature: training, development and education of teachers; 6. according to the organizational-structural criterion, the following models are distinguished: concurrent, consecutive and combined; 7. according to the certification criterion, the traditional and alternative models of teacher education are mentioned. However, the distinction drawn between the aforementioned models appears to be artificial, because their model-making features do not exclude each other, but are rather complementary. Applying chronological criterion is problematic as well, since every consecutive stage in the model's development incorporates the features of its predecessor model. Likewise, quality teacher education cannot do without adequate theoretical knowledge base, which constitutes the grounding of the applied science model, or practical teaching skills (art-craft model), creativity (viewing teaching as art), reflection, self-observation, analysis of teaching and learning (reflective model), as well as recognizing the role of socio-cultural, economic, political and other factors in education (critical model).